Epidemiological and Phylogenetic Investigation of Panton-Valentine Leukocidin-Positive Community-Associated Methicillin-Resistant Staphylococcus aureus in Ireland and Internationally using Whole-Genome Sequencing - Aloba, Bisola (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is a successful modern pathogen associated with many clinical manifestations including asymptomatic colonisation, superficial skin infections and severe invasive diseases. Over the last three decades, numerous MRSA clones have emerged worldwide within healthcare environments, the community and in livestock settings, many of which encode a wide variety of antimicrobial resistance (AMR) and virulence-associated genes. Panton-Valentine leukocidin (PVL)-negative sequence type (ST)-22-MRSA carrying staphylococcal cassette chromosome mec (SCCmec) element Type IV is the pandemic healthcare associated (HA)-MRSA clone in several European countries. In Ireland, ST22-MRSA-IV has predominanted in hospitals for over three decades, accounting for approximately 80% of all MRSA bloodstream infections. However, the prevalence of PVL-positive MRSA in Ireland has also gradually increased, with several outbreaks reported in neonatal intensive care units (NICU) and paediatric units. Studies reporting on the population structure of MRSA in Ireland have focused primarily on healthcare associations, neglecting potential reservoirs in the community. The epidemiological work presented in Chapters 3, 4 and 5 investigated the community associated (CA)-MRSA population in Irish hospitals and the association of these lineages with infection outbreaks using high resolution, short-read, Illumina MiSeq-based whole-genome sequencing (WGS). This work underscores the critical importance of on-going surveillance of MRSA to track circulating strains and monitor changing patterns. The first part of this study investigated multiple distinct outbreaks of PVL-positive CA-MRSA in several Irish hospitals (H1-H3) using WGS. Between 2011 and 2020, a total of 46 suspected outbreak-associated isolates were recovered from 36 individuals across three separate Irish hospitals and submitted to the national MRSA reference laboratory (NMRSARL) for analysis. Thirty-five of these isolates were from patients, one from a healthcare worker (HCW) and the remaining eleven isolates from members of two separate families, at least one member of each had received hospital H2-based treatment for MRSA infection. The 46 isolates underwent whole-genome multi-locus sequence typing (wgMLST) and single nucleotide polymorphism (wgSNP) genotyping. The previously suggested thresholds of ?24 wgMLST allelic differences and ?15 SNPs were used for inferring epidemiological relationships and close relatedness between S. aureus isolates. The investigation revealed two unrelated PVL-positive ST8-MRSA-IVa outbreaks within two separate Irish hospitals (H1 and H2) over a four-month period between 2017 and 2018. The wgMLST/wgSNP-based minimum spanning trees (MSTs) revealed two distinct clusters, CH1 (8/10 H1 isolates) and CH2 (6/6 H2 isolates). Within each cluster, neighbouring isolates were separated by ?5 allelic differences; however, ?73 allelic differences were identified between the two clusters, indicating two separate outbreaks. The occurrence of two distinct, concurrent MRSA outbreaks within a third hospital (H3, maternity hospital) over a 15-month period in 2018?2020 was also confirmed from wgMLST/wgSNP-based MSTs. Two separate isolate clusters, CH3-SCI (14/15 PVL-positive ST5-MRSA-IVc isolates) and CH3-SCII (4/4 PVL-negative ST88-MRSA-V isolates) were identified. Within each cluster, neighbouring isolates were separated by ?24 allelic differences, whereas the two clusters were separated by 1822 allelic differences, confirming two distinct H3 outbreaks. One of the H3 ST88-MRSA-V outbreak-associated isolates was recovered from a HCW working in this hospital, highlighting the involvement of HCWs in MRSA transmission events. Lastly, intra-familial transmission of PVL-positive ST1-MRSA-V+fus+tirS+ccrA1 and PVL-negative ST97-MRSA-V+fus was identified in two separate families associated with hospital H2. The presence of three separate clusters (FC1, FC2 and FC2) were observed from the wgMLST/wgSNP-based MSTs, FC1 (4/4 ST1 isolates from family 1 only), FC2-ST1 (4/4 ST1 isolates from family 2) and FC2-ST97 (3/3 ST97 isolates from family 2). Neighbouring isolates within each cluster were closely related and exhibited ?7 allelic differences. Although intrafamilial transmission was apparent, the detection of ?48 allelic differences between the clusters indicated no interfamilial transmission between the two separate families. As part of the CA-MRSA outbreak investigations, surveillance of the CA-MRSA population currently circulating in Irish hospitals was also carried out, primarily focused on CA-MRSA associated with maternity patients, as these are typically healthy individuals with minimal MRSA risk factors, including limited exposure to the healthcare environment. A total of 330 CA-MRSA isolates recovered between 2011 and 2022 from 13 different Irish hospitals (H1?H13) (N=326), a Dublin-based General Practitioner (GP) (N=2) and a regional GP (N=2) were investigated using core-genome multi-locus sequence typing (cgMLST). The population structure analysis revealed a diverse population of CA-MRSA in Irish hospitals, with 32 different STs and 91 different spa types identified. The isolates were predominantly ST1 (12.7%), ST5 (22.7%), ST8 (14.5%) and ST22 (18.4%), while the spa types mainly included t002 (13.4%), t008 (11%), t127 (12.2%) and t032 (7.3%). This investigation also highlighted a high prevalence of PVL-positive CA-MRSA (91/330, 27.6%) in Irish hospitals, reflective of global trends where PVL-positive CA-MRSA is continually increasing. The increasing introduction of PVL-positive CA-MRSA into healthcare settings, transmission and association with outbreaks is a serious concern. In recent years, multiple importations of multi-drug resistant (MDR) PVL-positive CA-MRSA clones have been reported, including the ST772-MRSA-V Bengal Bay clone and the ST8-MRSA-IV USA300 clone. A PVL-positive ST5-MRSA-IVc lineage associated with a protracted 15-month outbreak in H3 was found to exhibit genotypic similarities to previously described `Sri Lankan clone? isolates which were recently reported as emerging in a large teaching hospital in Sri Lanka, Australia and the UK. The second part of this study investigated the widespread dissemination and diversity of this novel CA-MRSA lineage across numerous disparate geographical regions over a 17-year period using WGS. Thirty PVL-positive ST5-MRSA-IVc isolates (including the 14 H3 outbreak-associated isolates) submitted to the NMRSARL between 2013 and 2022 were investigated. Additional PVL-positive ST5-MRSA-IVc clinical isolates (N=56) and WGS datasets (N=128 including 46 isolates from the Sri Lankan teaching hospital) recovered from eleven countries including Australia, Czech Republic, Denmark, Germany, Kuwait, Norway, Saudi Arabia, Sri Lanka, Sweden, UAE and the UK between 2005 and 2021 were also investigated. A majority (142/214, 66.4%) of the isolates were from infections, and where detailed metadata were available (168/214; 78.5%), slightly more than half were community associated (85/168, 51%). For comparative purposes, 29 PVL-positive and 23 PVL-negative ST5-MRSA-I/II/IVa/IVc/IVg/V isolates (N=41) and WGS datasets (N=11) for isolates recovered between 2003 and 2021 from Algeria, Australia, Czech Republic, Denmark, Germany, Ireland, Kuwait, Norway, Saudi Arabia, Senegal, Slovakia, Sri Lanka, Sweden, UAE and the UK were also investigated. The core-genome single nucleotide polymorphism (cgSNP)-based maximum likelihood tree (MLT) grouped 209/214 (97.7%) PVL-positive ST5-MRSA-IVc isolates into Clade I with an average of 110 cgSNPs between isolates. The five remaining PVL-positive ST5-MRSA-IVc isolates grouped into Clade III with an average of 92 cgSNPs. Clade II contained seven PVL-positive ST5-MRSA-IVa comparators, whereas the remaining 45 comparators formed an outlier group. A cgMLST-based MST revealed a comparably low average of 57 allelic differences between the 214 PVL-positive ST5-MRSA-IVc isolates. These isolates were identified as `Sri Lankan? clone, predominantly spa type t002 (186/214, 86.9%) with little population diversity which harboured a similar range of virulence genes and variable antibiotic resistance-encoding genes to one another. The association of Sri Lankan clone isolates with both community and hospital infections in 12 countries spanning 17 years reflects its widespread dissemination internationally and its potential to become a dominant CA-MRSA clone. The bacteriophage-encoded PVL cytotoxin is considered one of the most significant S. aureus virulence factors and is a genetic marker associated with many major CA-MRSA lineages. To date, several PVL-encoding bacteriophages with distinct structural organisations have been described lysogenised into the S. aureus chromosome. The third part of this study investigated the PVL-encoding bacteriophage lysogenised in the genome of the PVL-positive ST5-MRSA-IVc Sri Lankan clone. The assembled genomes of the Sri Lankan clone (N=214) and comparator (N=52) isolates described in the second part of this study were investigated for pvl-associated bacteriophage DNA. Twenty-six representative Sri Lankan clone isolates and eight comparator isolates also underwent Oxford Nanopore long-read sequencing and hybrid-assembly with the Illumina-based short-read sequences to further investigate the PVL-encoding phage genome. All 26 Sri Lankan clone isolates and seven Clade II comparators lacked an intact lysogenized PVL-encoding phage genome, but harboured a unique chromosomally integrated 9.6 kb PVL-encoding phage remnant. This remnant exhibited 100% sequence homology with the 3? junction of the well-characterized PVL-encoding phage ?Sa2wa. Using specially designed primers specific to the Sri Lankan clone PVL phage remnant, an in-silico PCR analysis was performed to screen the pubMLST database for additional strains harbouring this phage remnant. This pubMLST search resulted in ten PVL-positive ST5-MRSA-IVc, seven PVL-positive ST5-MRSA-IVa and one ST5-MSSA additional assembled genomes harbouring an identical 9.6 kb PVL-encoding phage remnant. A cgSNP-based MLT revealed that the ten ST5-MRSA-IVc pubMLST isolates grouped into Clade I with 209/214 of the ST5-MRSA-IVc Sri Lankan clone isolates with an average of 110 cgSNPs. The seven ST5-MRSA-IVa pubMLST isolates grouped with the seven ST5-MRSA-IVa comparators in Clade II with an average of 78 cgSNPs. The ST5-MSSA isolate branched out next to Clade III Sri Lankan clone isolates exhibiting between 196?240 SNPs to these isolates. These findings suggested that the ST5-MRSA-IVc Sri Lankan clone Clade I/III and the ST5-MRSA-IVa Clade II isolates all arose from a PVL-positive common ancestor harbouring the 9.6 kb phage remnant, very likely a PVL-positive methicillin-susceptible ancestor. The stable chromosomal integration of PVL in the Sri Lankan clone potentially contributes to its widespread dissemination. Additionally, this remnant may be a useful genetic marker for the Sri Lankan clone, as the earliest Sri Lankan clone study isolate recovered in 2005 also harboured the remnant. The application of WGS for MRSA epidemiological investigations is highly advantageous as it provides a highly discriminatory tool with unprecedented resolution for accurately tracking spread, monitoring transmission and investigating suspected outbreaks. The increasing prevalence of CA-MRSA, including MDR PVL-positive CA-MRSA lineages in the community and in hospital settings in Ireland is a serious cause for concern. This study highlighted the importance of local and international surveillance in monitoring the emergence and transmission of notable MRSA clones.
APPROVED
Keywords: Community-associated MRSA; Methicillin resistant Staphylococcus aureus; Panton?Valentine leukocidin; Whole-genome sequencing; Healthcare-associated infection outbreaks; Phylogenetics; Epidemiology; Dissemination; PVL cytotoxin